They Will Definitely Need Us, When We Are 64: Old-Age Provision in Germany - Martin Werding (Intereconomics)
Abstract Many countries followed the German example in increasing the legal retirement age, reaching the German standard envisaged for 2030 (of 67 years of age) at an earlier stage (in Ireland: 2021; the Netherlands: 2021; and Denmark: 2022) or even exceeding it (in Ireland: with 68 years, starting in 2028).